Role of digital transformation for sustainable competitive advantage of SMEs: a systematic literature review - Huie Lu; Muhammad Shabir Shaharudin (Cogent Business & Management, 2024)
The digital revolution has fundamentally changed how businesses create value. Small and medium enterprises (SMEs), with their limited resources, must adapt to this new landscape to maintain a competitive edge through digital transformation (DT). This paper explores how SMEs can build sustainable competitive advantage (SCA) via DT. Using the WOS Core Collection database, we conducted a comprehensive review and bibliometric analysis, examining 1,856 articles on SCA, with a detailed focus on 57 that specifically address DT. The findings show that DT enhances SMEs' innovation and dynamic capabilities, helping them overcome resource constraints and better respond to market shifts. Key digital technologies such as big data, artificial intelligence, and digital platforms are crucial in driving these results. Practical insights are also offered for SMEs managers to tailor digital strategies, optimize operations, and build SCA.
Keywords: 650; Small and medium enterprises (SMEs); Sustainable competitive advantage; Digital transformation; Digital strategy; Systematic literature review